Green Procurement and Government Policy as Catalysts for Enhancing Organizational Performance in Nigeria’s Fast-Moving Consumer Goods Sector - Yadua, Joy; Nwoye, May Ifeoma; Ibrahim, Umar Abbas (Indonesian Scientific Publication, 2026)
This paper examines how green procurement and government policy affect the performance of Fast-Moving Consumer Goods (FMCG) companies in Nigeria. While sustainability is gaining global relevance, limited empirical evidence addresses how these drivers influence firm outcomes in Nigeria. The study investigates the extent to which green procurement and government policy shape organisational performance in the FMCG sector. A cross-sectional survey was conducted with 357 supply chain personnel across some listed FMCG firms. Data were analysed using ordinary least squares regression to establish the impacts of the variables. The regression results show that sustainable manufacturing (β = 0.192, p < 0.001) had the strongest positive effect on performance, followed by reverse logistics (β = 0.164, p < 0.001), Government policy (β = 0.133, p = 0.001), and green packaging (β = 0.117, p = 0.001). The model explained 41.2% of performance variation. Firms need to embed green procurement by strengthening supplier evaluation, investing in capacity-building, and ensuring transparent sourcing. Policymakers should enforce regulations consistently and introduce fiscal incentives to promote sustainability, while stakeholders collaborate to align practices with long-term sectoral performance goals.